Colombian government employs CCAFS-validated model for methane emissions to elaborate a sustainable livestock strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The validation of a model to estimate animal nutrition and energy losses by feeding with different forages allowed the government of Colombia to develop mitigation options for a Nationally Appropriate Mitigation Action (NAMA) for livestock and Colombia's livestock federation, FEDEGAN, to implement a sustainable livestock strategy targeting 50,000 ha of degraded pastures.